Influence of Interest In Learning and How to Learn on Understanding Concepts: Work and Energy Cases - Alvi Hasanati*; Endang Purwaningsih (Jurnal Pendidikan Sains Indonesia, 2021)
Student who do not have an interest in lessons will find it difficult to achieve optimal success, and the way students learn also affects student learning outcomes. The research aims to determine the effect of interest in learning and how students learn in understanding student concepts. The type of research used is survey research. The  research subjects were 60 students of class X Ar-Rohmah Islamic Boarding School Dau Malang. The research instrument was adapted and developed from previous research.The concept understanding instrument was adapted from the Energy Concept Assessment and Energy and Momentum Conceptual survey questions. Data processing using multiple regression analysis. The data analysis technique used multiple regression analysis. The data analysis results show that the value of Fcount = 46,946 Ftable = 4.001, these results indicate that there is an influence on students' interest in learning with concept understanding. Obtained the results of testing how to learn and understanding the concept of Fcount = 55.364 Ftable = 4.001, it can be concluded that there is an influence on student learning and conceptual understanding. Furthermore, the results of testing the effect of student interest in learning and learning methods on concept understanding were obtained Fcount = 40.153 Ftable = 3.150, so that there was an effect of interest in learning and learning methods on understanding the concept of business and energy theory